Pelatihan Crafting Keychain Sebagai Sarana Pengembangan Karakter Dan Kreasi Anak Yayasan Mizan Amanah Krukut - Rizki Ruliyana; Faradilla Azzahra Putri; Revina Febryani Gunawan (Journal of Conflict and Social Class (JCSC), 2026)
This community service journal aims to describe the implementation of keychain crafting training as a medium for character development and creativity enhancement for children at the Mizan Amanah Foundation. The background of this activity is the limited access of foster children to creative and character-based skill development activities. The objective of this program is to foster creativity, independence, discipline, and self-confidence through simple craft activities. The method used was participatory training involving demonstrations, guided practice, and evaluation of the work produced by participants. The results show that children were able to produce keychain crafts independently and demonstrated positive changes in attitudes such as patience, cooperation, and enthusiasm during the activity. This training proves to be effective as an alternative educational approach that integrates creativity and character building. The program also provides practical skills that can be developed into productive activities in the future.